Container Traffic In European Ports - Twrdy, Elen (Promet - Traffic&Transportation, 2004)
Over the last fifteen years the European transport markethas witnessed a growth of container traffic which today reachesapproximately 50 million TEU per year. From 1997 to 2002,container traffic in the northern European ports increased from14 to 20.6 million TEU per year, in the ports of the westernMedite’anean from 6 to 10 million TEU per year, and in thenorthern Adriatic ports from 0. 69 to 0. 74 million TEU per year.The ports of the northern Adriatic are located in three states(Slovenia, Croatia and Italy) with different statuses in relationto the common European market. In addition, different developmentlevels of these states are reflected in different levels ofinternational commercial exchange, the development of the existinginfrastructure and plans for the construction of new infrastructures.However, all three countries share a common goaltoincrease their competitiveness in comparison with the westemEuropean ports.